Feminisms : the basics - Heberle, Rene??e, 1962- (Routledge, 2026)
This introduction presents, in a readable, lively style, an overview of feminism as an essentially contested field of theory and political engagement. Renee Heberle offers readers a unique approach to studying feminisms in the plural, combining historical and theoretical perspectives on the academic and political lives of the term "feminism." While the popular imagination identifies feminism in the singular with political activity about women's rights, this book introduces readers to diverse, historically significant, critical perspectives and interventions. Heberle's approach demonstrates the ongoing relevance of feminisms to contemporary political thinking and practice. This book will be particularly useful in upper-division undergraduate classrooms and introductory courses at the graduate level of study. It is written in an accessible narrative form that will also appeal to the non-academic reader.Key Features: Reviews the historiography of the term "feminism" and perspectives and activism associated with the term. Introduces feminisms for their value in understanding complex dynamics of domination and power from interdisciplinary perspectives. Explains differences among self-identified feminists as thinkers and activists historically and in the contemporary moment. Serves as an excellent springboard for classroom discussions of the nature and purpose of feminisms as complex and contested field of theories and practices Discusses contemporary work by Brittney Cooper, Sarah Ahmed, Nevedita Menon, and Veronica Gago to set up questions about how/why each contemporary author identifies as a feminist and what they describe as feminism. Shows how integral feminisms have become to academic, institutional and public understandings of historical and contemporary events and dynamics. Feminisms: The Basics is a fresh introduction to our understanding of feminisms and feminist theories.
Keywords: Feminism.; elektronické knihy; electronic books